1951
DOI: 10.1172/jci102430
|View full text |Cite
|
Sign up to set email alerts
|

The Anemia of Thermal Injury. I. Studies of Pigment Excretion 12

Abstract: Our interest in the metabolism of hemoglobin in patients with thermal injury was stimulated by early observations that (a) in spite of multiple whole blood transfusions anemia often developed rapidly in the first 96 hours after injury, and (b) in the protracted convalescence of a patient with only a small burn, moderate anemia inevitably ensued. The latter was exceptionally refractory to all except replacement therapy. With these two facts in mind we have undertaken our present study of the burn patient in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1951
1951
1983
1983

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This was in striking contrast to similar studies to be described later in the burned man where there were significant changes in serum iron, copper, and free erythrocyte protoporphyrin (vide infra). Figure 4 (dog 29) shows the same changes in fecal urobilinogen excretion and urinary coproporphyrin excretion which have been described in man following burns (1). From the time of the injury to the 10th day there was an increased fecal urobilinogen output.…”
Section: Methodssupporting
confidence: 60%
See 1 more Smart Citation
“…This was in striking contrast to similar studies to be described later in the burned man where there were significant changes in serum iron, copper, and free erythrocyte protoporphyrin (vide infra). Figure 4 (dog 29) shows the same changes in fecal urobilinogen excretion and urinary coproporphyrin excretion which have been described in man following burns (1). From the time of the injury to the 10th day there was an increased fecal urobilinogen output.…”
Section: Methodssupporting
confidence: 60%
“…of nitrogen and sufficient calories to maintain body weight under control conditions. Hemo- 1 This study was conducted under Contract Number DA 49-007-MD-99 between the Office of the Surgeon General, Department of the Army, Washington, D. C., and the Medical College of Virginia, Richmond, Virginia.…”
Section: Methodsmentioning
confidence: 99%
“…The anemia which develops following thermal burns and the occurrence of a continuing anemia in burned patients and animals has been a frequent finding (1)(2)(3)(4). Studies in this laboratory have indicated that in burned rats there is a rapid reduction in circulating red cell volume following high intensity radiant energy thermal burns (4).…”
mentioning
confidence: 99%
“…This reduction in red blood cell volume is followed by a period of increased red cell production as shown by the return of the circulating red cell volume to normal and by a significant reticulocytosis. Clinical studies in severely burned patients (2,3) have revealed evidence of an immediate reduction in the circulating red cell volume and frequently a continuing reduction of the red cell volume.…”
mentioning
confidence: 99%
“…In a previous communication it was demonstrated that an increased excretion of urine urobilinogen was an early and constant finding in thermal injury even in burns of a relatively small amount of third degree (1). Since this particular finding was interpreted by us as a manifestation of hepatic injury, we undertook the further study of certain liver function tests in burned patients, none of whom received sulfonamides, tannic acid or other escharing therapy.…”
mentioning
confidence: 97%